The fused deposition modeling of POFA reinforced composites polymer - Darsani, Adilah (2021)
Palm oil fuel ash (POFA) is one of the waste products in the palm oil industry, whereas the abundance of that waste largely contributed to environmental effects. A strong interest in the development of renewable products to reduce the environmental effects has been focusing on the use of waste source as reinforcements in polymer matrix composites. In 3D Printing Fused Deposition Modeling (FDM), composite filament material has started to be used in the pattern development application. However, in FDM pattern development, the composite filament has a common issue especially in reference to the nozzle clogging problem that relates to the critical process in composition mixing and filament preparation. Therefore, this research aims to investigate the capability of different percentage composition in the range of 20vol% - 60vol% of POFA with polypropylene (PP) materials formed into solid composite filament for FDM machine. The composite materials were mixed homogeneously using the Brabender mixer machine and the addition of 5vol% and 8vol% maleic anhydride grafted polypropylene (MAPP) as a compatibilizer to improve the bonding ability of the PP matrix and POFA as well as to improve flowability during the next process. The Melt Flow Index (MFI) test was conducted on POFA+PP+MAPP compositions to investigate the data of viscosity which is important for the filament extrusion process. The single screw extrusion machine was used in the fabrication of composite filaments with a diameter and length range of 1.70 ± 0.02mm and 60 to 70cm respectively. Then, the filaments were run for deposition test on the FDM machine by printing the ISO527-1 (dog bone sample). Finally, the properties in terms of mechanical and surface observation were investigated for the successful printed sample. The investigation results of the POFA filament deposition test on FDM shows that 40vol% POFA, 55vol% PP, and 5vol% MAPP gave the highest tensile strength which is 27.40MPa compared to other composition and virgin PP, 20% net increment of elongation at break compared to 20%vol POFA, lower warping defect and high initial degradation temperature with 318ºC.